2007
DOI: 10.1111/j.1600-0528.2006.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and childhood obesity: roles of diet and socioeconomic status

Abstract: Caries and obesity coexist in children of low socioeconomic status. Public health measures to improve dietary education and access to appropriate foodstuffs could decrease the risk of both diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
2
26

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(214 citation statements)
references
References 51 publications
8
175
2
26
Order By: Relevance
“…5,[8][9][10]15,19,[22][23][24]27,29,33,36,40,41 Eight studies included adjustments for age and sex, 6,19,23,27,29,33,36,41 two only for sex, 15,22 and fi ve for consumption of any type of food, such as soft drinks, 10,24 fruits or snacks between meals, 10 "fast food", 10 and milk, 9 as well as daily sugar consumption 19 and "snack" consumption more than three times a day. 29 Among the 28 articles, 13 were considered to have good scientifi c evidence according to the criteria of Downs & Black.…”
Section: Resultsmentioning
confidence: 99%
“…5,[8][9][10]15,19,[22][23][24]27,29,33,36,40,41 Eight studies included adjustments for age and sex, 6,19,23,27,29,33,36,41 two only for sex, 15,22 and fi ve for consumption of any type of food, such as soft drinks, 10,24 fruits or snacks between meals, 10 "fast food", 10 and milk, 9 as well as daily sugar consumption 19 and "snack" consumption more than three times a day. 29 Among the 28 articles, 13 were considered to have good scientifi c evidence according to the criteria of Downs & Black.…”
Section: Resultsmentioning
confidence: 99%
“…102 A recent study of 427 children in the Iowa Fluoride Study found a positive association between obesity and caries in those from families of low socio-economic status. 103 However, regardless of obesity, low socio-economic status is a known caries risk factor. 32,104 Intake of sweet drinks as a component of caries risk assessment in children…”
Section: Sweet Drinks and General Health Of Childrenmentioning
confidence: 99%
“…In addition, Werner et al (2012) reported an association between obesity and caries in the primary teeth but did not explain why obese/overweight children had fewer caries. Studies have found dental caries and obesity coexisting among children with low family income (Marshall et al, 2007) and that those having high dental caries experience and high BMI are found to share similar behavioral practices (Cinar and Murtomaa, 2011). These findings might be an explanation for the association between dental caries and obesity.…”
Section: Discussionmentioning
confidence: 82%